The language of the end or La vida ausentet. About a book by Ángel Zapata (XXI Century. Spanish Literature and Culture, 2020)
In La vida ausente, the unique book of prose by Ángel Zapata, tales, surrealist prose writings and micro-narratives, reminiscent of automatic writing—with lyrical overtones and tinges of the absurd—live together in harmony. In short, as the author likes to say, aesthetics and life are intertwined in order to oppose the kind of power which seeks to control desire. It is not surprising, then, that his works are part of a tradition that runs from classical to contemporary writers like Kafka, Breton,  Peret, Lorca, the humorists of ’27, with Mihura as their principal representative; the humanized absurd of Becket and Javier Tomeo, and Quim Monzó.
Keywords: Ángel Zapata; short story; micro-narrative; surrealism; the absurd